(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
In India, almost 61 percent of all death in India is due to lifestyle disorders and non-communicable diseases WHO identifies prime risk factors for LSD. These are alcohol and tobacco intake, poor diet intake, lack of physical activities, mental stress, etc. According to sustainable development goal l3.4, which mandates a 1/3rd reduction in premature death due to lifestyle disorder by 2030. An individual or group of people who have a lifestyle disorder (LSD) are essentially inviting themselves to develop any number of ailments that are mostly based on how they live. These include conditions including chronic bronchitis, hypertension, heart disease, stroke, obesity, diabetes, and malignancies brought on by diet and cigarette use. Ayurveda describes several principles to prevent LSD like Dincharya (daily routine), Ritucharya (seasonal routine), Sadvratta (code of conduct), etc but seven principles are essential to follow to lead a healthy life. These are 1. Tri-upstairs (Ahara, Vihara, Brahmacharya) which is the main pillar of health, 2. Dincharya, 3. Ritucharya, 4. Avoidance of Vegadharana (suppression of natural urges), 5. Avoidance of Prajnapradha (renunciation) 6. Sadvratta (good code of conduct), 7. Yoga (to avoid mental stress). This article mainly emphasizes the preventive aspect of Lifestyle disorder by using the Ayurveda principle.